2018
DOI: 10.1111/bcp.13483
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin for the prevention of severe preeclampsia: where next?

Abstract: Low molecular weight heparin has been extensively evaluated for the prevention of preeclampsia in high-risk pregnant women; however, the results from these trials have been conflicting. This review discusses the potential mechanisms of action of low molecular weight heparin for the prevention of severe preeclampsia, how to optimize the selection of high-risk women for participation in future trials, and the importance of trial standardization. Preeclampsia preventionPreeclampsia is a hypertensive disorder of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 60 publications
0
16
0
2
Order By: Relevance
“…Therefore, based on the most up‐to‐date evidence, LMWH cannot be recommended for the prevention of FGR in women at high risk of placenta‐mediated complications. Its use for the prevention of FGR should therefore be limited to research settings, for example in women already on aspirin who are found to have abnormal levels of angiogenic markers prior to fetal viability 142 …”
Section: Early Prediction and Prevention Of Fetal Growth Restrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, based on the most up‐to‐date evidence, LMWH cannot be recommended for the prevention of FGR in women at high risk of placenta‐mediated complications. Its use for the prevention of FGR should therefore be limited to research settings, for example in women already on aspirin who are found to have abnormal levels of angiogenic markers prior to fetal viability 142 …”
Section: Early Prediction and Prevention Of Fetal Growth Restrictionmentioning
confidence: 99%
“…Its use for the prevention of FGR should therefore be limited to research settings, for example in women already on aspirin who are found to have abnormal levels of angiogenic markers prior to fetal viability. 142…”
Section: Biochemical Markersmentioning
confidence: 99%
“…Pregnant women treated, or not, with heparin in the current study did not show differences in the frequency of preeclampsia. However, other studies have associated higher frequency of hypertensive syndromes in pregnant women with thrombophilia, as well as better fetal outcomes, with heparin treatment [20][21][22][23][24]. The small number of patients, as well as lack of knowledge about the severity of the clinical case in this subgroup (preeclampsia), may have made such evaluation difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Недопустимо планирование продленной ИВЛ на несколько суток в условиях глубокой седации, так как в этих условиях оценка состояния ЦНС без дополнительных методов исследования крайне затруднена. Не рекомендовано для профилактики ПЭ рутинное применение: режима bed-rest (дозированного постельного режима) [33], диуретиков [34], препаратов группы гепарина, в том числе низкомолекулярных гепаринов [35], хотя в последние годы появились единичные сообщения о возможной эффективности низкомолекулярных гепаринов для профилактики ПЭ [36], витаминов Е и С [37], рыбьего жира [38], чеснока [39], прогестерона [40], сульфата магния [40], фолиевой кислоты [40].…”
Section: наиболее распространенные диагностические и тактические ошибunclassified